Inventory of damage to coastal and marine ecosystems in the Kepulauan Riau, Indonesia - Mosriula Mosriula (Sekolah Tinggi Ilmu Pertanian Wuna, 2019)
Research on an inventory of damage to coastal and marine ecosystems of the Riau Islands was carried out in the waters of the Berakit Village of Bintan Regency and Pulau Pasir Batam City. The purpose of this study was to obtain data on the status and condition of damage to seagrass coastal marine ecosystems and coral reefs in the two locations. The research period is from May to July 2019. The research method uses 'quadrant line transect' and Underwater Photo Transect and GIS analysis. Distribution of seagrass ecosystems 981.65 Ha, coral reefs 4291.73 Ha in Bintan Regency and Batam City. Berakit Beach seagrass cover has an average of 36.55% in the damaged or less rich / unhealthy category, while 71.02% in the Sand Island is in the dense or rich / healthy category. For live coral cover, Berakit Beach is 42.87% of medium condition category, while Pasir Island has an average of 1-2% of damaged condition category.